Sports Stadium Chemnitz 2002 - Peter Kulka (Oz, 1998)
Our proposal for the Chemnitz Stadium demonstrates a vision of a light, transparent roof structure over a contoured hill-marked landscape. In between sits the Tribunal as a sculptural object.